Heart stopping tick - Karmacharya, Paras (Baishideng Publishing Group Co., Limited, 2013)
Although Lyme carditis is relatively rare within 4-6 wk of exposure, it can uncommonly present as the first sign of disseminated Lyme disease. Here we present 17 year old boy who presented to the emergency department with chest discomfort and was later found to have complete atrioventricular block due to lyme carditis. He had uneventful recovery after empiric treatment with ceftriaxone. Our case highlights the importance of considering reversible causes of complete AV block since appropriate therapy can avoid the need for permanent pacemaker insertion.